The Effect of Political Elections on Stock Market Volatility in Malaysia - Chia Chee Jiun, Ricky (International Journal of Engineering and Technology, 2018)
During the past general elections held in Malaysia, empirical evidence showed a significant election effect in stock volatility. In this study, we investigate the influence of election on Malaysian stock market during the 12th and 13th general election where political tensions persisted due to the close fight between the two major parties. The findings indicate that the political uncertainty surrounding elections significantly affected investors respond. Results from statistical analysis uncover significant higher stock volatility in the pre-general election periods. Nevertheless, lower stock volatility is only found in two stock indices in the post-general election periods. By using the EGARCH model, a significant election effect is found in stock volatility but not in stock returns. Notably, political uncertainty showed up its significant role in influencing the stock volatility prior to the general elections in the year 2008 and 2013. Furthermore, lower stock volatility is found in the Shariah-compliant indices and stock index with greater market capitalization. Our findings have important implications for investors who are exposed to volatility risk. Investors may shift to large company stock and Shariah-compliant stock during the general election period. Investors should also be cautious because the high volatility is not compensated with a significant abnormal return.Â